Symptoms characteristics of personality disorders associated with suicidal ideation and behaviors in a clinical sample of adolescents with a depressive disorder - Anthony Joseph Gifuni; Anthony Joseph Gifuni; Michel Spodenkiewicz; Michel Spodenkiewicz; Michel Spodenkiewicz; Geneviève Laurent; Sasha MacNeil; Sasha MacNeil; Fabrice Jollant; Johanne Renaud; Johanne Renaud (Frontiers in Psychiatry, 2023)
IntroductionPathological personality traits have repeatedly been identified as important risk factors for suicidal ideation and behaviors. Moreover, impulsive-aggressive traits, have shown a consistent association with suicidal behaviors across the lifespan. Adolescence represents a critical period for the emergence of different personality traits, mood disorders, and suicidal behaviors, but the relationship between these variables remain poorly understood.MethodsThese variables were examined in a cross-sectional case–control design involving three groups: 30 adolescents with a depressive disorder and past suicide attempt (Mean Age = 16.2, Females = 26), 38 adolescents with a depressive disorder but without past suicide attempt (Mean age = 16.0, Females = 29), and 34 healthy adolescent controls (Mean age = 15.2, Females = 22). Suicidal ideations were indexed using Suicidal Behavior Questionnaire (SBQ-R), psychiatric disorder assessed using a semi-structured questionnaire (K-SADS-PL), depressive symptoms with the Beck Depressive Inventory (BDI), symptoms characteristics of personality disorders with the Scheduled Clinical Interview for the DSM-IV (SCID-II) screening questionnaire, and impulsivity with the Barratt Impulsivesness Scale (BIS).ResultsFindings showed that impulsivity (F = 11.0, p < 0.0001) and antisocial symptoms characteristics of personality disorders (p < 0.001, d = 0.70) displayed the most robust association with adolescent suicide attempts. Borderline symptoms characteristics of personality disorders did not discriminate attempters from non-attempters but presented high correlations with suicidal ideation and depression severity. In an item-wise analysis, suicide attempt status was uniquely correlated with symptoms characteristics of an antisocial personality disorder. Suicide attempt status also correlated with non-suicidal self-injury and a chronic feeling of emptiness.DiscussionThe caveats of this cross-sectional study include the stability of symptoms characteristics of personality disorders in adolescence and the limited sample size. In sum, suicidal behaviors were characteristically correlated with increased impulsivity and antisocial symptoms characteristics of personality disorders, but other symptoms characteristics of personality disorders were relevant to adolescent depression and suicidal ideation. Understanding the emergence of symptoms characteristics of personality disorders and suicidal behaviors in a developmental context can ultimately inform not only the neurobiological origin of suicidal behaviors, but also provide new avenues for early detection and intervention.